Does the bracket composition material influence initial biofilm formation? - Gustavo Antônio Martins Brandão; Antonio Carlos Pereira; Ana Maria Martins Brandão; Haroldo Amorim de Almeida; Rogério Heládio Lopes Motta (Indian Journal of Dental Research, 2015)
Context: Orthodontic treatment has been reported to contribute to the development and accumulation of dental biofilm, which is commonly found on bracket and adjacent surfaces. Aims: The aim of this work is to test the hypothesis if there are differences in dental biofilm formation on the surface of orthodontic brackets according to the type of composition material. Subjects and Methods: Three bracket types (metallic, composite, and ceramic) had been evaluated. Subjects wore acrylic palatal orthodontic appliances, containing 6 brackets each, for two 3-day cycles. On the end of first cycle, the amount of dental biofilm formed on the samples was extracted using 1.0-M NaOH and analyzed by spectrophotometry for quantification. An additional cycle was carried out to verify the dental biofilm formation using scanning electronic microscope analysis. Statistical Analysis Used: Three-way ANOVA was used to analyze the difference among the materials (metallic, ceramic and composite) concerning the dental biofilm absorbance spectrum. Multiple comparisons were made using the Tukey′s test (α =0.05). Results: Composite brackets showed greater values concerning biofilm formation, when compared with the metallic and ceramic ones, both of which presented similar scores. The hypothesis is accepted. There are differences on the biofilm formation according to the type of material. Conclusions: The in situ model tested was found to be effective in evaluating the accumulation and development of biofilm on orthodontic brackets. In the quantitative analysis, composite brackets showed greater biofilm adhesion values while metallic and ceramic presented similar biofilm absorbance spectrum.